In Vitro and In Vivo evaluation of montmorillonite for paraquat poisoning - Xiang Guo; Wei Guo; Tiandi Li; Fen Liu; Jinpeng Zhou; Meiqiong Guo (Universidade de São Paulo, 2023)
Abstract Evaluation of montmorillonite for paraquat by in vitro and in vivo test. In vitro test were evaluated by a batch test, taking the paraquat concentration, adsorbents, reaction environment and time as indices, the absorption rate was screened by orthogonal design. In vivo test was executed with rabbits. Group 1: 4 rabbits dosed with montmorillonite. Group 2: 8 rabbits dosed with 200 mg/kg paraquat. Group 3: 6 rabbits dosed with 200 mg/kg paraquat then gavage with montmorillonite 5 min later. Group 4: 6 rabbits dosed with 200 mg/kg paraquat then gavage with montmorillonite 30 min later. Blood paraquat concentration, serum cytokines, blood gas analysis and histopathology of lung were implemented. In vitro test found that all the four factors influence the absorption rate of paraquat (P < 0.05). In vitro test found that oral montmorillonite could change toxicokinetics parameters of paraquat (P < 0.05); decrease raised serum TGF-β1 and HMGB1 (P < 0.05) and alleviate the histopathology damage of lung. Montmorillonite might exert its protective effects on paraquat induced damage.